Identifikasi Model Pengelolaan Lahan Kering Dataran Tinggi Berbasis Agroforestri Tradisional di Pulau Timor - Yakobus Pffeferius Edvend Saba Agu; Eduardus Y. Neonbeni (Fakultas Pertanian, Universitas Timor, 2019)
The purpose of the study are; (i) to identify the traditional management models based on dry upland agroforestry; (ii) to measure the value of community household income on each traditional agroforestry model based on dry upland management. The research was conducted in West Miomaffo, North Timor Tengah, Timor Island, East Nusa Tenggara in October-December 2016. The method used descriptive exploratory, date collected by observation techniques, questionnaires, and direct interviews toqey person. Sample determined by land use existing map based on overlaying the landsat image and the ecological agroforestry distribution on the Timor Island. To find the economic contribution of the community (The number of) respondents determined by snowball sampling. The results of the study there are three traditional agroforestry models that are developed by the community; (a) namely kono agrosilvicultur model which is a practice of sedentary cultivation with the composition of woody, annual trees, and crops; (b) agrosilvopasture poan model which is a permanent forest garden practice with a high variety of plant species (Polycultur) as well as management forms that resemble the shape of forest gardens with diverse canopy stratification; (c) silvopastural suf model, is a practice of natural grazing in the savanna region, which is used as a natural livestock ranch. The household income contribution analysisis known to be above 50%, means that the three traditional agroforestry models has the opportunity to be developed. The needs of intensive interference to sustainable management by considering the regional ecology, socio-economic and local wisdom.